WACANA NON DOMINAN: MENGHADIRKAN FIKIH ALTERNATIF YANG BERKEADILAN GENDER - Kau, Sofyan A.P.; Suleman, Zulkarnain (Al-Ulum, 2013)
Fikih kaya atas keragaman opini hukum, termasuk fikih perempuan. Opini hukum fikih tentang perempuan tidak tunggal melainkan beragam. Keragaman fikih perempuan ini sejatinya menjadi pilihan alternatif atas fikih yang berperspektif gender. Tulisan ini menawarkan wacana non dominan sebagai fikih alternatif untuk menghadirkan fikih yang berkeadilan gender. Sebab wacana dominan tentang fikih perempuan dikritik sebagai fikih yang tidak berkeadilan gender. Sementara fikih tidak hanya menghadirkan wacana dominan, melainkan juga menyandingkan wacana non dominan. Dalam wacana non-akikah dan cara membersihkan air kencing bayi laki-laki dan perempuan disamakan. Bersentuhan dengan perempuan tidak membatalkan wudhu, dan perempuan memiliki hak yang sama dengan lelaki dalam hal perwalian, saksi dan kepemimpinan. Dalam wacana non dominan, perempuan boleh menjadi wali dan saksi pernikahan, imam salat jamaah dan pemimpin publik. -----------------Jurisprudence has a diversity of opinions over the law interpretation. Among other is the women jurisprudence. Furthermore, the women legal opinion is subsequently not single but diverse. The diversity of women jurisprudence is actually seen as an alternative, that is, âgenderâ perspective kind of fiqh. This paper offers a non-mainstream discourse over the fiqh by presenting and assessing âgenderâ perspective kind of jurisprudence. This is done because it is seen that most discourse over women jurisprudence were dominated by gender inequality; and therefore it should be thoroughly criticized. With the exception of akiqah discourses, the way to bath boysâ and girlsâ urine, they both treated equally the same. Any physically contacts with women subsequently do not invalidate the ablution (wudhu). Therefore, woman has equal rights with man in custody, witness and leadership. More importantly, in the non-dominant discourse of jurisprudence, woman may be a guardian and a witness to a wedding, even can be a khutbah priest and an imam of public congregational prayers.